Tuck seine fishing in Laguna De Bay. - Gutierrez, Oscar E. (College of Fisheries, University of the Philippines, 1951)
Locally known as Pukot Laot, this tuck seine is operated commercially in Laguna De Bay. This is of great value to the fishermen and people residing there for the fresh water fishes and other aquatic products have been caught abundantly through this means. But though this gear has been so used profitably it is significantly noted through the operation of this gear that any substitution may be had in order that complete satisfaction will be afforded to the people. It is then the purpose of this paper to describe the operation, construction and the prospectus, etc. of this gear.